Implementation Of The PERSIJU Program (Half-Day Friday Camp) For The Project Of Strengthening The Pancasila Student Profile In Early Childhood Education - Laela Laela; Imron Arifin; Pramono Pramono; Eny Nur Aisyah; Ajeng Putri Pratiwi (Green Publisher Indonesia, 2024)
Preschool Children are children who still need examples and direction in carrying out daily activities. Considering that ages 5-6 years interact more with the environment around them. One of the PERSIJU activities (Friday Half Day Camping) which is routinely held every 2 weeks. Persiju is an activity that gives children freedom to interact, practice socializing and practice independence and solidarity with their friends. The aim of this research is to train children's independence, socialization and hone the social skills of children aged 5-6 years as well as supporting and inhibiting factors. The research method used is qualitative. Data collection techniques are observation, interviews with supervisors, school principals and class teachers and documentation. The results of the research show that children are very enthusiastic about taking part in Persiju activities held at school, children actively participate in a series of Persiju game activities both independently and in groups which are carried out outside the classroom with the teacher. The role and support or permission of parents is one of the supporting factors in training independence, as well as honing the social skills of children aged 5-6 years, social skills that appear to include conversation, mutual understanding, cooperation, openness, empathy, motivation, positive feelings and feelings of equality. The inhibiting factor is facilities and infrastructure that still need to be added.